2006
DOI: 10.1021/ja063485l
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Detection of Enantiomers

Abstract: The rapid quantification of the enantiomers of small chiral molecules is very important, notably in pharmacology. Here, we show that the enantiomers of drug molecules can be distinguished by stochastic sensing, a single-molecule detection technique. The sensing element is an engineered alpha-hemolysin protein pore, fitted with a beta-cyclodextrin adapter. By using the approach, the enantiomeric composition of samples of ibuprofen and thalidomide can be determined in less than 1 s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 34 publications
2
139
1
3
Order By: Relevance
“…Our results will be useful in several areas of basic science and biotechnology. By using host molecules lodged within the αHL pore, host-guest interactions can be investigated in fine detail at the single-molecule level (17,49). The present work will now permit us to examine binding events at a known face of a CD.…”
Section: Resultsmentioning
confidence: 96%
“…Our results will be useful in several areas of basic science and biotechnology. By using host molecules lodged within the αHL pore, host-guest interactions can be investigated in fine detail at the single-molecule level (17,49). The present work will now permit us to examine binding events at a known face of a CD.…”
Section: Resultsmentioning
confidence: 96%
“…If just one recognition site were to be used, it might be possible to sharpen R 2 by additional mutagenesis (with both natural and unnatural amino acids) and by site-directed chemical modification, and further blunt the other sites (48). Certainly, the exquisite ability of (context independent) stochastic sensing to distinguish between molecules (14,49) shows what can be done with nanopores under the most favorable conditions. In the case of solid-state nanopores, it has been suggested that an active property of translocating bases (such as the ability to carry tunneling currents) might be used for sequencing (10,(50)(51)(52), but no practical demonstration of such a technique has been made.…”
Section: Single-nucleotide Discrimination Within a Heteropolymeric Sementioning
confidence: 99%
“…3 Blocking currents enable the electrical identification of distinct molecular configurations and the elucidation of mechanisms responsible for single molecule behavior, such as single molecule transport, 4 protein unfolding, 5 and DNA unzipping. 6 Therefore, this method has been attracting attention as a next-generation of DNA sequencing or a single-molecule detection technique.…”
Section: Introductionmentioning
confidence: 99%